Proximal median nerve neuropathy: electrodiagnostic and ultrasound findings in 62 patients - Shields, Lisa B. E.; Iyer, Vasudeva G.; Zhang, Yi Ping; Shields, Christopher B. (Frontiers in Neurology, 2024)
ObjectivesProximal median nerve (PMN) neuropathies are caused by lesions proximal to the carpal tunnel, which include the forearm, elbow, upper arm, and brachial plexus. Differentiating between carpal tunnel syndrome and PMN neuropathies is important to guide management and is based on clinical, electrodiagnostic (EDX), and ultrasound (US) findings. This study describes the clinical, EDX, and US features in 62 patients with PMNs.MethodsAll patients underwent EDX studies, and 52 (83.9%) had a US study. The patients were assigned to one of the following four localization zones of PMN neuropathies based on clinical and EDX criteria: Zone 1: extends from the fascicles in the brachial plexus contributing to the median nerve to the innervation of the pronator teres (PT); Zone 2: distal to the branch to the PT and proximal to the origin of the anterior interosseous nerve (AIN); Zone 3: involves the origin of the AIN; and Zone 4: distal to the origin of the AIN and proximal to the carpal tunnel. The localization was based on the pattern of muscle weakness, topography of EMG abnormalities, and US study findings.ResultsThe anatomical locations of the PMN neuropathies based on clinical, EDX, and US findings were as follows: Zone 1 in 38 patients (61.3%), Zone 2 in 6 patients (9.7%), Zone 3 in 7 patients (11.3%), and Zone 4 in 11 patients (17.7%). The most common etiology among all 62 patients was iatrogenic injury (30 [48.4%]), followed by non-iatrogenic trauma (20 [32.2%]). The following EDX findings were noted: prolonged distal motor latency (29 [46.8%]), decreased motor nerve conduction velocity in the forearm (22 [35.5%]), low amplitude or absent compound muscle action potentials (50 [80.6%]), and abnormal or absent sensory nerve action potentials (50 [80.6%]). Of the 52 (83.9%) patients who underwent US studies, a total of 22 (42.3%) patients showed an increased cross-sectional area of the median nerve. A neuroma was observed in 9 patients (17.4%).ConclusionIt is often possible to localize the site of the median nerve involvement and gain insight into the underlying cause based on clinical and EMG findings, but in certain cases, a US study may be necessary to confirm the location.